Avaliação das unidades de separação e valorização de resíduos sólidos urbanos de Curitiba e região metropolitana, PR, Brasil - Trombetta, Gilmara Raquel (2011)
Management activities of solid urban waste seek to develop actions that solve the issue of solid waste, in its various aspects, seeking the proper conditions in order to reach its sustainable development which will result in the improvement of the environment and quality of life. Management has found a technique in the separation for posterior recycling which has the potential to minimize the environmental and socio-economical impacts cause by waste. This process is developed in the Separation Units of Solid Urban Waste. The Separation Units seek minimization, social inclusion, reduction of the grounding impact, and the waste of natural resources. However, there are few units, and there working conditions are insanitary, with inadequate infrastructure and present several problems in the separation process and commercialization. In light of these facts a survey was conducted with the objective to evaluate the real conditions of the Separation Units of Waste in Curitiba and Metropolitan Regions. The survey was conducted in 26 municipalities located in the Metropolitan region of Curitiba, utilizing the method of case study, with technical visits and a questionnaire with structured questions, open and closed, in 10 municipalities, and was sent via email, to other 16 municipalities. In total 23 municipalities participated in the survey. In these sites we observed the situation regarding the infrastructure, the labor and separation process. We tried to create performance indicators for further evaluation of the separation process. We observed that the units lack in proper and adequate equipment and location; most of the workers are female; the working conditions are poor and insanitary in most of the locations, due mainly to the lack of local management, as well as problems and inefficiencies in the waste separation process. It was verified that the positive and negative aspects according to the managers’ evaluation, were the same as the general evaluation. There is a lack of efficient public policies, and of qualified personnel for the procedure, that is, a lack of trained technicians and managers to operate in these units. Through this performance evaluation of the process it was also verified that out of the 11 units assessed, not one presented a high level of performance: 45% of the units had an average performance and 55% presented poor performance. On the other hand, it was noted that if well administrated, units reach high percentages of separation and consequently add value to the waste, and promote social-economic inclusion of individuals who are unemployed, homeless, drug users, and discriminated by society. The proper management of the units promotes environmental gains through the reduction of the grounding of spoils which also reduces the extraction of raw material.